The study of e-waste management awareness among students of UiTM Seremban 3 / Syahrul Eidham Mohamed Nazree, Muhammad Aizul Aswad Amir and Farah Adilla Ab Rahman - Mohamed Nazree, Syahrul Eidham; Amir, Muhammad Aizul Aswad; Ab Rahman, Farah Adilla (Universiti Teknologi MARA, Sabah, 2022)
This research aims to learn about university students' knowledge, and attitudes about the existence, danger, and management of e-waste, one of the world's fastest-rising concerns in our country. It also tried to evaluate whether the students' current e-waste management practices conformed with current government policies. Six (6) of the Bachelor Degree of Environmental Administration students' awareness about e-waste management in Malaysia was evaluated using an open-ended interview research technique. The respondents' knowledge, attitude, and practice in e-waste management were assessed using thematic analysis. Overall, students' understanding of e-waste management was relatively low. The findings indicate that students need a broader understanding of e-waste management. Educational and government-led initiatives to improve e-waste management should be provided.